Severity of U.S. Construction Worker Injuries, 2015-2017 - Passmore David; Chae Chungil; Borkovskaya Victoria; Baker Rose; Yim Jeong-Ha (E3S Web of Conferences, 2019)
Workers in the U.S. construction industry experience workplace hazards that can lead to work-related injuries that sometimes are fatal. Reported in this paper is a case-control study of risks factors associated with 4,845 injured workers and their work environments that led to fatal rather than nonfatal injuries during 2015-2017. These injury data originally were assembled from information collected by the U.S. Bureau of Labor Statistics that were used in a machine learning competition, but were repurposed for this secondary analysis of injury risks. Sixty-one percent of workers recorded in this dataset were injured fatally. Multiple logistic regression was applied to model the probability of a fatal injury as a function of the nature of the injury, part of body injured, human factors involved, whether the injured worker was carrying out a regularly assigned task at the time of the injury, and the manner in which the injury was inflicted. Related positively, relative to benchmarks, to the probability of a fatality injury were: falls and strikes; electrocution; asphyxiation and drowning; injury to the head and neck; and working at a task not regularly assigned. Negatively related to the probability of a fatal injury were: chemical/temperature burns; amputation and crushing; fractures and dislocations; injuries to fingers, hands, wrists, and other extremities; and falls from an elevation or to the same level, although this last negative relationship is anomalous in the light of independent research findings. Findings of this study do not necessarily culpable causes of work-related death. Rather these findings identify risk factors that might prove fruitful for further analysis of the incidence, severity, and costs of construction injuries.